Perbedaan Jumlah Akseptor KB Hormonal pada Masa Sebelum Pandemi, Pandemi dan New Normal COVID-19 di RB Citra Palembang - Meta Rosdiana; Rina Puspita (Indonesian Journal of Midwifery (IJM), 2022)
During the COVID-19 pandemic, health care resources were used to obtain masks, virology services, personal protective equipment, ventilators, building a special covid field hospital, and morgues. Emergency COVID-19 care takes up the time, resources, and space that would normally be used for routine care. The loss of reproductive health services, which some governments consider unimportant, poses significant challenges for health care providers and women of reproductive age. During the lockdown period, working from home, isolation, and other restrictions have hampered access to health services including contraceptive services. These factors can cause millions of unplanned pregnancies, millions of unsafe abortions and result in thousands of deaths. In 2010-2014, an estimated 44% of pregnancies worldwide were not undesirable and this figure could increase during the COVID-19 pandemic. People are afraid to come to the hospital or health care center cause of contracting COVID-19. This is not much different from the number of family planning acceptors in the maternity hospital and independent practice midwives, which makes mothers afraid to get midwifery services, especially for women who accept hormonal family planning, which has short-term effectiveness, which requires the acceptor to return to a health care provider. This research is to find out the difference in the number of hormonal family planning acceptors during the pre-pandemic, pandemic, and New Normal periods at the Citra Palembang Maternity Hospital. A cross-sectional design, the sample of this study is all the number of hormonal family planning acceptors in the pre-pandemic, pandemic, and New Normal period at the Citra Palembang Maternity Hospital in the period 12th December 2019-27th August 2020. Pre-pandemic is the normal period before the COVID-19 pandemic in Indonesia (during the pandemic 12th December 2019 to 1st March 2020. (79 days). The pandemic started when the Indonesian president first announced the first case of COVID-19 in Indonesia on March 2nd, 2020. The pre-pandemic period is from March 2nd to May 19th, 2020. (79 days). New normal Started when the Indonesian government issued a health protocol for the New Normal situation on May 20th, 2020, through the Decree of the Minister of Health. May 20th, 2020, to August 27th, 2020. (79 days). Data of family planning acceptors in pre-pandemic, 124 oral acceptors, 317 acceptors as 1-month injections, 419 acceptors as 3-months injections, and 16 implant acceptors. During the pandemic, 30 oral acceptors, 80 acceptors 1-month injections, 90 acceptors as 3-months injections, and 4 implant acceptors. New normal COVID-19, 45 oral acceptors, 100 acceptors as 1-month injections, 100 acceptors as 3-month injections, and 3 implant acceptors. This study concludes that all hormonal family planning visits decrease during the pandemic, this is because of the COVID-19 pandemic, people are reluctant to leave the house because of the risk of contracting COVID-19, especially to come to health service providers.Abstrak Masa pandemi COVID-19 sumber daya perawatan kesehatan digunakan untuk mendapatkan masker, layanan virologi, alat pelindung diri, ventilator, membangun rumah sakit lapangan khusus COVID-19, dan kamar mayat. Perawatan darurat COVID-19 menyita waktu, sumber daya, dan tempat yang biasanya digunakan untuk perawatan rutin. Selama masa Pembatasan Sosial Berskala Besar (PSBB), bekerja dari rumah, isolasi, dan pembatasan lainnya telah menghambat akses pelayanan kesehatan termasuk layanan kontrasepsi. Pada 2010-2014, diperkirakan 44% kehamilan di seluruh dunia tidak diinginkan dan angka ini dapat meningkat selama masa pandemi COVID-19. Pandemi di Indonesia membuat kekhawatiran masyarakat untuk datang ke fasilitas kesehatan. karena takut tertular COVID-19. Perlu diberikan edukasi kesehatan yang tepat dan lengkap agar masyarakat yang memang membutuhkan layanan kesehatan non COVID-19 tidak takut berobat ke pelayanan kesehataan. Hal tersebut tidak jauh berbeda dengan jumlah akseptor KB pada rumah bersalin dan bidan praktek mandiri yang membuat ibu takut untuk mendapatkan pelayanan kebidanan, khususnya bagi wanita akseptor KB hormonal. Terlebih untuk KB hormonal yang memiliki jangka efektivitas pendek yang mengharuskan akseptor untuk kembali lagi ke penyedia layanan kesehatan. Tujuan penelitian ini untuk mengetahui perbedaan jumlah akseptor kb hormonal pada masa sebelum pandemi, pandemi dan New Normal COVID-19 di Rumah Bersalin Citra Palembang. Desain penelitian cross sectional, sampel penelitian ini adalah semua jumlah akseptor KB Hormonal pada masa sebelum pandemi, pandemi dan New Normal COVID-19 di Rumah Bersalin Citra Palembang pada rentang waktu 12 Desember 2019- 27 Agustus 2020. Sebelum pandemi bila melakukan kunjungan KB pada 12 Desember 2019 sd 1 Maret 2020. Masa Pandemi, bila melakukan kunjungan KB pada 2 Maret sd 19 Mei 2020. New normal COVID-19, bila melakukan kunjungan KB pada 20 mei 2020 sd 27 Agustus 2020. Data akseptor KB sebelum pandemi, pil 124 akseptor, KB 1 bulan 317 akseptor, KB 3 bulan sebanyak 419 akseptor, dan akseptor KB implan 16 akseptor. Masa pandemi, PIL 30 akseptor, KB 1 bulan 80 akseptor, akseptor KB 3 Bulan 90 akseptor, dan akseptor KB implan 4 akseptor. Masa new normal COVID-19, pil 45 akseptor, akseptor KB 1 bulan 100 akseptor, akseptor KB 3 Bulan sebanyak 100 akseptor, dan akseptor KB implan 3 akseptor. Kesimpulan hasil penelitian ini memiliki hasil yang seragam yakni bahwa semua kunjungan KB hormonal menurun pada masa pandemi, hal ini karena keadaan pandemi COVID-19 masyarakat membatasi diri keluar rumah karena beresiko tertular COVID-19, terlebih untuk datang ke penyediaa layanan kesehatan.